Reactivation of hepatitis B virus in cancer patients treated with chemotherapy for solid tumors. Is the prophylaxis really required?. Issue 2 (February 2017) - Federico, Alessandro; Brancaccio, Giuseppina; Dallio, Marcello; Iodice, Patrizia; Fabozzi, Alessio; Del Prete, Salvatore; Ciardiello, Fortunato; Loguercio, Carmela; Gaeta, Giovanni Battista
Abstract: Background: Reactivation of hepatitis B virus during cancer chemotherapy for non-hematological tumors is not fully clear. Aim: To evaluate the risk of hepatitis B virus reactivation in carriers of hepatitis B virus cancer patients treated with chemotherapy for solid tumors. Methods: Two hundred sixty-seven patients with solid tumors were consecutively enrolled: 13 (4.8%) were hepatitis B s-antigen positive, of whom 6 were documented inactive carriers and 7 had chronic liver disease. Thirty-two patients (12%) were hepatitis B s-antigen negative/hepatitis B c-antibody positive. Hepatitis B virus inactive carriers were followed every 3 months by alanine aminotransferases, hepatitis B virus-DNA; whereas hepatitis B virus occult carriers were followed every 3 months by alanine aminotransferases and hepatitis B s-antigen. Results: None of the 38 total patients with inactive or occult B infection who did not receive prophylaxis presented hepatitis B virus reactivation during the follow-up period. Conclusion: This study suggests that, in hepatitis B s-antigen negative patients who undergo chemotherapy for solid tumors, hepatitis B and c-antibody screening results are not relevant to clinical decision and can be avoided. Larger studies are needed to establish whether the risk of reactivation of HBV during chemotherapy is negligible in this subset of patients and they could not be monitored for HBV reactivation.